Determination of seismic soil–structure interaction in shear-wall buildings on sloping ground (Gaceta Técnica, 2026)
In structural practice, it is common to assume rigid foundations when modelling structures. However, this simplification neglects the actual effects of soil–structure interaction (SSI), which may lead to underestimation of the seismic response. This study evaluates such interaction in mid-rise shear-wall buildings located on slopes of 0°, 15°, 30°, and 45°, through nonlinear dynamic analyses performed using SeismoStruct. Real Chilean seismic records, including those from Angol and Valparaíso, among others, were applied, incorporating link-type models in accordance with FEMA P-2091 to represent dynamic stiffnesses. Displacements, interstory and global drifts, shear forces, and structural damage were analyzed. The results show that SSI and ground inclination significantly influence the dynamic response of the system, particularly in structures with high lateral stiffness. This study provides practical recommendations for seismic design in areas with irregular topography, promoting a more realistic representation of structural behavior
Keywords: soil–structure interaction; nonlinear seismic analysis; structures on sloping ground